Dynamic changes in sperm flagellum during fertilization - Jabloñski, Martina (2022)
Mammalian sperm undergo a series of biochemical and cellular changes in thefemale reproductive tract to acquire fertilizing ability. These changes arecollectively known as capacitation. As a result, sperm lose the acrosome in aprocess called acrosomal exocytosis (AE). Most of the studies are conducted invitro, using a mixture of acrosome-intact and reacted sperm withoutdiscriminating the acrosomal status.